Efficacy and Safety of BCG Vaccine for Control of Tuberculosis in Domestic Livestock and Wildlife - Buddle, Bryce M.; Vordermeier, Hans Martin; Chambers, Mark A.; de Klerk-Lorist, Lin-Mari (Frontiers in Veterinary Science, 2018)
Bovine tuberculosis (TB) continues to be an intractable problem in many countries, particularly where “test and slaughter” policies cannot be implemented or where wildlife reservoirs of Mycobacterium bovis infection serve as a recurrent source of infection for domestic livestock. Alternative control measures are urgently required and vaccination is a promising option. Although the M. bovis bacille Calmette-Guérin (BCG) vaccine has been used in humans for nearly a century, its use in animals has been limited, principally as protection against TB has been incomplete and vaccination may result in animals reacting in the tuberculin skin test. Valuable insights have been gained over the past 25 years to optimise protection induced by BCG vaccine in animals and in the development of tests to differentiate infected from vaccinated animals (DIVA). This review examines factors affecting the efficacy of BCG vaccine in cattle, recent field trials, use of DIVA tests and the effectiveness of BCG vaccine in other domestic livestock as well as in wildlife. Oral delivery of BCG vaccine to wildlife reservoirs of infection such as European badgers, brushtail possums, wild boar, and deer has been shown to induce protection against TB and could prove to be a practical means to vaccinate these species at scale. Testing of BCG vaccine in a wide range of animal species has indicated that it is safe and vaccination has the potential to be a valuable tool to assist in the control of TB in both domestic livestock and wildlife.